The modified water swallowing test score is the best predictor of postoperative pneumonia following extubation in cardiovascular surgery: A retrospective cohort study. Issue 4 (29th January 2021) - Oguchi, Natsuko; Yamamoto, Shuhei; Terashima, Satsuki; Arai, Ruka; Sato, Masaaki; Ikegami, Shota; Horiuchi, Hiroshi
Abstract : Abstract: No guidelines have been established for the evaluation of swallowing function following extubation. The factors of bedside swallowing evaluations (BSEs) that are associated with the development of pneumonia have not been fully elucidated. This study aimed to retrospectively investigate the most appropriate measurements of BSEs for predicting pneumonia. The study subjects were 97 adults who underwent BSEs following cardiovascular surgery. Patients were divided into the pneumonia onset group (n = 21) and the non-onset group (n = 76). Patient characteristics, intraoperative characteristics, complications, BSE results, and postoperative progress were compared between the groups. BSEs were composed of consciousness level, modified water swallowing test (MWST) score, repetitive saliva swallowing test score, speech intelligibility score, and risk of dysphagia in the cardiac surgery score. Univariate and multivariate analyses with the BSE as the independent variable and pneumonia onset as the dependent variable were also performed to identify factors that predict pneumonia. For factors that became significant in univariate analysis, the incidence of pneumonia was shown using the Kaplan-Meier curve. No significant differences were found in patient characteristics, intraoperative characteristics, and complications between the 2 groups. The postoperative progress was significantly different between the 2 groups, the pneumonia-onset group had a significantly longer time until the start of oral intake and a significantly lower median value of Food Intake Level Scale at the time of discharge. According to univariate and multivariate analyses, MWST score was a significant factor for predicting the onset of pneumonia even after adjusting for patient characteristics and surgical factors, and the incidence of pneumonia increased approximately 3 times when the MWST score was 3 points or less. The MWST score after extubation in cardiovascular surgery was the strongest predictor of postoperative pneumonia in BSEs. Furthermore, the incidence of pneumonia increased approximately 3 times when the MWST score was 3 points or less. Predicting cases with a high risk of developing pneumonia allows nurses and attending physicians to monitor the progress carefully and take aggressive preventive measures.